2013
DOI: 10.4321/s1886-36552013000200001
|View full text |Cite
|
Sign up to set email alerts
|

Advancing interprofessional education through the use of high fidelity human patient simulators

Abstract: *Background: Modern medical care increasingly requires coordinated teamwork and communication between healthcare professionals of different disciplines. Unfortunately, healthcare professional students are rarely afforded the opportunity to learn effective methods of interprofessional (IP) communication and teamwork strategies during their education. The question of how to best incorporate IP interactions in the curricula of the schools of health professions remains unanswered. Objective: We aim to solve the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 12 publications
1
44
0
6
Order By: Relevance
“…27 A subsequent report described the use of human patient simulation during an IPE scenario involving 5 different disciplines and its impact on communication, but only 8 students were involved in this feasibility study. 28 The introduction of high-fidelity human patient simulation in the school of nursing was perceived as an opportunity to develop IPE experiences between the 2 schools and to increase pharmacy students' exposure to human patient simulation. To overcome the barriers of coordination of student class schedules and participation among all students of a graduating class, faculty members from both programs collaborated to determine the appropriate courses within the 2 curricula to include an IPE curricular initiative facilitated by human patient simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 A subsequent report described the use of human patient simulation during an IPE scenario involving 5 different disciplines and its impact on communication, but only 8 students were involved in this feasibility study. 28 The introduction of high-fidelity human patient simulation in the school of nursing was perceived as an opportunity to develop IPE experiences between the 2 schools and to increase pharmacy students' exposure to human patient simulation. To overcome the barriers of coordination of student class schedules and participation among all students of a graduating class, faculty members from both programs collaborated to determine the appropriate courses within the 2 curricula to include an IPE curricular initiative facilitated by human patient simulation.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another described 1 pharmacy school's efforts to increase their IPE curriculum using human patient simulation with teams representing 5 disciplines. 28 With the introduction of human patient simulation in the nursing and pharmacy curricula at Wilkes University, faculty members were seeking to create opportunities to use this technology in an IPE experience among students in the 2 schools. Therefore, we created the first IPE clinical laboratory within the curricula of both programs.…”
Section: Introductionmentioning
confidence: 99%
“…5 The majority of this evidence includes the use of highfidelity mannequin simulation instruction. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A number of outcomes (eg, self-perceived clinical skills, teamwork and interprofessional teamwork skills, blood pressure assessment) have been assessed using high-fidelity mannequins. Although it has been shown that high-fidelity mannequin simulation can increase knowledge retention in pharmacy education, data is lacking on retention of advanced cardiac life support (ACLS) knowledge and skills following simulation training.…”
Section: Introductionmentioning
confidence: 99%
“…This technology provides learners with a safe environment to practice skills, refine knowledge, and engage with other health care professionals in an interprofessional team environment. 11 Using HPS as a teaching and learning strategy has been incorporated at the University of Pittsburgh School of Pharmacy since 2006. [12][13][14] Use of HPS for ID content has been limited in the literature to antimicrobial administration as a precipitant for anaphylaxis management.…”
Section: Introductionmentioning
confidence: 99%